Gong dalam Budaya Masyarakat di Indonesia - Wahyu Sri Wiyati; Saptono Saptono; Anis Raharjo (Institut Seni Indonesia Denpasar, 2023)
Purpose: This paper aims to briefly discuss the existence of the gong as a traditional musical instrument which has taken root in the lives of most people in Indonesia, which began with the development of bronze culture. The vast power of the Majapahit kingdom and inter-island trade, known as the silk route trade, greatly influenced the spread of Gong in the archipelago. Research Method: This phenomenon is discussed through the perspective of art studies as a form of traditional society's need for gong which is considered to have regius value as a means of ceremonies and goods for traditional needs so that gong spreads very quickly to remote areas of the interior. It is very possible that Gong is traded by bartering or exchanging forest and mining products such as: spices, agarwood, rattan, bird's nests, gold, diamonds and so on. Results and discussion: The existence of three types of gong forms in the archipelago, both those with high sides, low sides and non-pencu gongs, as well as forms of large and small ensembles show a very important identity for each community or ethnic group. Melodic gongs arranged horizontally show differences from gongs arranged in a semicircle such as those in Burma, Vietnam, Cambodia and Thailand. The different forms of gongs and ensembles will of course color the diversity of forms of Indonesian culture, especially in the field of traditional music. Implication: This article is an initial investigation of the existence of gongs in the archipelago with the hope that they can become material for appreciation and education for the younger generation in Indonesia. The gap between traditional culture, especially the Gong music ensemble, which was once a part of people's lives in the past, seems to urgently need attention, both by the government, art colleges, artists, cultural observers and the younger generation of music owners.